2023
DOI: 10.35580/btl.v5i2.41840
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Problem-Based Learning (PBL) Terhadap Keterampilan Berpikir Kritis Siswa SMA pada Materi Perubahan Lingkungan

Abstract: Abstract. The purpose of this study was to determine the effect of a problem-based learning model (PBL) on the critical thinking skills about changes in the environment. This study adopted a quasi-experimental model with a non-equivalent group design. The subjects of this study are 10th students at SMA Negeri 1 Genteng for the 2020/2021 school year. The sampling technique used purposive sampling and chose 30 students in each of the experimental and control classes. Critical thinking skills data collection usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Based on the results of the study of the ten articles on point 1 in the result. It was found that the PBL model showed positive effect in improving students' critical thinking skills (Agnesa & Rahmadana, 2022;Dakabesi & Luoise, 2019;Hermawan, 2022;Kasmiati et al, 2020;Marhamah et al, 2020;Pusparini et al, 2021;Setiawan & Islami, 2020;Wenno et al, 2021;Windari & Yanti, 2021;Yulfiani & Muchlis, 2021). In addition, the effect of the PBL model on critical thinking skills was also found in the medium category (Pujianti & Rusyana, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the study of the ten articles on point 1 in the result. It was found that the PBL model showed positive effect in improving students' critical thinking skills (Agnesa & Rahmadana, 2022;Dakabesi & Luoise, 2019;Hermawan, 2022;Kasmiati et al, 2020;Marhamah et al, 2020;Pusparini et al, 2021;Setiawan & Islami, 2020;Wenno et al, 2021;Windari & Yanti, 2021;Yulfiani & Muchlis, 2021). In addition, the effect of the PBL model on critical thinking skills was also found in the medium category (Pujianti & Rusyana, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the pretest-posttest results of students obtaining a percentage of N-Gain score ≥0.3, and 90.63% of students are in the high category, and 9.38% are in the medium category. Hermawan (2022) The sig value was obtained based on the study's results by calculating independent sample t-test statistical tests on critical thinking skills. = 0.000 < sig.…”
Section: Wenno Et Al (2021)mentioning
confidence: 99%